The influence of silica fume on the apparent activation energy of HPC mixtures - Barbosa, Mônica Pinto [UNESP]; Pinto, Roberto C.A.; Peres, Luciano Donizete Pantano [UNESP] (My University, 2005)
The use of the maturity approach has been increasing in various fields of concrete construction. In order to estimate the development of a mechanical property of the concrete mixture reliably, it is necessary to previously determine the apparent activation energy of the mixture. This thermal sensitivity index is a function of several parameters including cement type, presence of admixtures, and w/c. This study investigates the influence of silica fume on the apparent activation energy of high-performance concrete mixtures. Following the procedure in ASTM C 1074, various mortar mixtures were prepared with 6 different types of Brazilian cements (CP-I-S, CP-IIF-32, CP-II-Z-32, CP-III, CP-IV-RS e CP-V-ARI), and with addition of silica fume at two levels (8% and 16% of cement mass). The results indicate that the presence of silica fume increases the value of the apparent activation energy.
Keywords: Activation energy; Cement; Maturity method; Silica fume